2021
DOI: 10.35741/issn.0258-2724.56.4.3
|View full text |Cite
|
Sign up to set email alerts
|

Influences of Quality of Life and Social Capital on Depression Among Laotian Migrant Workers in Northeast Thailand

Abstract: Migrant workers usually encounter socio-economic and living hardships resulting in complex physical, social, and mental health problems. This research aimed to determine the influence of quality of life (QOL) and social capital on depression among Laotian migrants working in the Northeast of Thailand, which has not been studied on such issues before. This cross-sectional study analyzed the data from the previous study related to the quality of Life of Laotian Migrant Workers in the Northeast of Thailand, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
0
0
Order By: Relevance
“…the study found that the Cambodia migrant workers encountered a number of problems such as discrimination, financial burden on document fee and daily expense during the earlier period of their arrival, inaccessibility of health service as they had no health insurance, and too long process of legalization. This result is partly consistent with the previous studies by Laohasiriwon et al ( 2020) and Kongsrima et al (2021) in which many aspects which lead to low quality of life was obviously found. These problems need to be tackled soonest as they are the foundation of human basic need (Danesh, 2011).…”
Section: Living Condition Of Cambodian Migrant Workerssupporting
confidence: 93%
“…the study found that the Cambodia migrant workers encountered a number of problems such as discrimination, financial burden on document fee and daily expense during the earlier period of their arrival, inaccessibility of health service as they had no health insurance, and too long process of legalization. This result is partly consistent with the previous studies by Laohasiriwon et al ( 2020) and Kongsrima et al (2021) in which many aspects which lead to low quality of life was obviously found. These problems need to be tackled soonest as they are the foundation of human basic need (Danesh, 2011).…”
Section: Living Condition Of Cambodian Migrant Workerssupporting
confidence: 93%